Correction: Corrigendum: EPPS rescues hippocampus-dependent cognitive deficits in APP/PS1 mice by disaggregation of amyloid-β oligomers and plaques - Hye Yun Kim (Nature Portfolio, 2016)
Nature Communications 6: Article number: 8997 (2015); Published: 8 December 2015; Updated: 15 February 2016 This Article contains errors in Figs 3 and 4. In Fig. 3h, the x axis should have been labelled ‘TG’, and in Fig. 4a, labels denoting the EPPS dose for each image were inadvertently removed. The correct versions of these two figures follow.